Analysis Of Information Technology Services Management Using ITIL V3 Domain Service Operation (Case Study: Hotel Sinar Sidoarjo) - Nur Hasan Assobarry; Fariza Nanda Sabila; Siti Mukaromah (IJCONSIST JOURNALS, 2022)
Information system is one of the most rapid developments of information technology in its development. This information system itself aims to help human work to be more efficient and effective. The quality of technology has many aspects that must be measured to evaluate in order to continue to develop. Service is an important aspect that needs to be improved in order to support the applied Information Technology. ITIL as a framework that focuses on the assessment of information technology services was chosen as the method to be applied in this research. The problem that often occurs in this Sinar Hotel is the existence of obstacles in customer data in the Front Office department. Customer data is often not inputted into the system so that customers have to re-enter data and this is time consuming and less efficient. The incoming data also sometimes does not match the customer's personal data which also results in the customer needing to re-enter the data. The Service Operation domain was chosen to assess the extent to which the problem management and incident management processes were implemented properly. The results of this study will produce a recommendation to overcome problems and incidents that often occur in order to facilitate the operational activities of Hotel Sinar.